Transformasi Digital Dalam Pengembangan E-Business Di Perbankan Syariah - Anni Aisyah Hidayani Siregar; Ratu Raissyah Apriliani; Murni Tafrijah; Nurbaiti . (CV. ITTC INDONESIA, 2026)
This study aims to analyse the implementation of digital transformation in the development of e-business in Indonesian Islamic banking, with a case study focus on Bank Syariah Indonesia (BSI). Digital transformation has become a strategic necessity for Islamic banking to increase competitiveness in the era of the 4.0 industrial revolution, but its implementation must remain in line with Islamic principles such as fairness, transparency, and the prohibition of usury. This study uses a descriptive qualitative approach through a literature review, analysing scientific journals, official BSI reports, and policy documents related to the digitalisation of Islamic banking. Data analysis techniques use content analysis with document triangulation to increase the validity of the findings. The results show that BSI has implemented comprehensive digital transformation through the BYOND platform, integration with halal fintech, a cloud-based core banking system, and the application of Artificial Intelligence and Big Data Analytics technologies. This implementation has successfully increased active users by 41% and operational efficiency by up to 28%. However, there are significant challenges faced, including customer digital literacy gaps, cyber security threats, the complexity of post-merger system integration, and the limited number of human resources who are proficient in Sharia-based digital technology. This study contributes to the literature on Islamic finance digitalisation by providing an understanding of how Islamic banking can transform sustainably without abandoning fundamental Sharia values.